Biliary atresia associated with pancreaticobiliary maljunction - Tatsuma Sakaguchi; Yoshinori Hamada; Takeshi Shirai; Hiroshi Hamada; Takashi Doi (Elsevier, 2018)
We report here two cases of Kasai type IIIa biliary atresia (BA), associated with pancreaticobiliary maljunction (PBM). Both cases were referred to our hospital because of hyperbilirubinemia and diagnosed with BA preoperatively by abdominal ultrasonography and biliary scintigraphy. They underwent Kasai portojejunostomy at 49 and 37 days old, respectively. Intraoperative cholangiographies performed from their gallbladders clarified Kasai type IIIa BA with PBM. Laboratory test of colorless fluid from the gallbladder of one patient showed high level of lipase (460 U/L). Reported cases of BA associated with PBM are rare and this is a second report showed elevated level of a pancreatic enzyme in bile. The findings in our cases indicate the pathogenesis of biliary anomaly in association with PBM. Keywords: Kasai type IIIa biliary atresia, Pancreaticobiliary maljunction, Infantile obstructive cholangiopathy